2018
DOI: 10.4314/tjpr.v16i12.10
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reverses type 2 diabetes-induced cognitive deficits via attenuation of oxidative/nitrosative stress and NF-κB-mediated neuroinflammation in rat hippocampus

Abstract: Purpose: To evaluate the protective effect of melatonin on diabetes-induced cognitive dysfunction. Methods: Rats were fed a high-fat diet + streptozotocin (HFD + STZ) for 15 weeks to induce type 2 diabetes (HFD + STZ group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…30 Moreover, the treatment with melatonin (10 mg/kg) in type 2 diabetic rats for 3 weeks caused a significant decrease in reactive oxygen species (ROS), oxido-nitrosative stress markers, including thiobarbituric acid reactive substances (TBARS), nitrite, and depleted glutathione (GSH) levels in the hippocampus of melatonintreated group. 31 It is suggested that melatonin is one of the most functional scavengers of free radicals. Melatonin acts as a direct scavenger and neutralizes several free radicals such as singlet oxygen, superoxide anion radical, hydroxyl radical, hydroperoxide, lipid peroxide radical, and peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, the treatment with melatonin (10 mg/kg) in type 2 diabetic rats for 3 weeks caused a significant decrease in reactive oxygen species (ROS), oxido-nitrosative stress markers, including thiobarbituric acid reactive substances (TBARS), nitrite, and depleted glutathione (GSH) levels in the hippocampus of melatonintreated group. 31 It is suggested that melatonin is one of the most functional scavengers of free radicals. Melatonin acts as a direct scavenger and neutralizes several free radicals such as singlet oxygen, superoxide anion radical, hydroxyl radical, hydroperoxide, lipid peroxide radical, and peroxynitrite.…”
Section: Discussionmentioning
confidence: 99%
“…Since the concept of DE was proposed by Nieleson in 1965, our understanding of DE has deepened. Its pathogenesis involves various aspects, including neuroinflammation (2, 3), blood-brain barrier (BBB) (2), vascular factors (4), insulin resistance, insulin deficiency (5, 6), and oxidative stress (3, 6). However, controversy in the literature remains.…”
Section: Introductionmentioning
confidence: 99%